2023
DOI: 10.3390/horticulturae9040509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seaweed-Based Biostimulants on Growth and Development of Hydrangea paniculata under Continuous or Periodic Drought Stress

Abstract: To adapt to climate change and water scarcity during dry, hot summers, more sustainable, or even deficit, irrigation is required in the ornamental sector, as it uses large amounts of water to sustain high-value crop production. Biostimulants, especially seaweed extracts, could offer a sustainable solution against drought stress as they are known to increase plant tolerance to abiotic stress. The effect of four seaweed extracts based on Ascophyllum nodosum, Soliera chordalis, Ecklonia maxima, and Saccharina lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
(81 reference statements)
3
3
0
Order By: Relevance
“…When used in urban and urbanised environments, Bistep biostimulant treatment can greatly improve the resistance and physical properties of the variety (stronger, thicker leaves), which is also an outstanding ornamental feature. These results are similar to results measured with other shrub species [17][18][19][20]. The results of Werner and Lefi [10,11] showed that a high phytohormonal activity was observed for the Kelpak ® algal product.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…When used in urban and urbanised environments, Bistep biostimulant treatment can greatly improve the resistance and physical properties of the variety (stronger, thicker leaves), which is also an outstanding ornamental feature. These results are similar to results measured with other shrub species [17][18][19][20]. The results of Werner and Lefi [10,11] showed that a high phytohormonal activity was observed for the Kelpak ® algal product.…”
Section: Discussionsupporting
confidence: 89%
“…The results with Photinia 'Red Robin', commonly used in urban environments, are similar to those with W. florida 'Eva Rathke', where [17] found no suitability for Kelpak ® in ornamental nursery containers. The results are similar to those obtained with Hydrangea paniculata, also an ornamental shrub [20].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Seaweed extracts contain plant hormones, such as cytokinins and auxins, which advance cell division during the early stages of plant growth and can induce early and more vigorous flower formation [41]. There are many reports on the beneficial effects of A. nodosum extracts on reproductive phenology, fruit production, and quality in different crops [59,60], including that of Phylgreen ® [61,62]. In our study, the two biostimulants tested favoured flowering, increasing the number of flowers formed in plants irrigated at field capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Standard soil application of fertilizers in nursery production can also be supported with appropriate biostimulants. Annual hydrangea plants exposed to water stress were treated with seaweed-based biostimulants in an attempt to reduce the stress [33]. The plants of Hydrangea paniculata treated with the biostimulants had the same number of branches and the same fresh weight as those that were not exposed to the stress.…”
Section: Introductionmentioning
confidence: 99%